ALTERNATIF PENYELESAIAN SENGKETA (APS) PERSPEKTIF AL-QURÁN DAN HADITS - Fuad Fatkhu Rakman; Syufa'at Syufa'at (IAIN Syekh Nurjati Cirebon, 2023)
AbstractThis study aims to find out the basis for Alternative Dispute Resolution (APS) which includes mediation, negotiation, conciliation, and arbitration in Islamic law taken from the Al-Qur'an and Al-Hadith. The core of the problem to be uncovered in this study is to find models of dispute resolution at the time of Rasulullah SAW. The research method used in this research is a library study research model with a descriptive qualitative approach and relies on books, articles, journals, and turots as a source of research data. The results of this study found that during the time of Rasulullah SAW and his companions, the practice of resolving disputes through Alternative Dispute Resolution (APS) had been found. This is evidenced by, first, the discovery of the basis for negotiation, mediation, conciliation, and arbitration from the Al-Qur'an and Hadith, second, the prophet Muhammad SAW negotiated with Suhail Bin 'Amr as a negotiator of the polytheists in the form of a hudaibiyah agreement, the three prophets of Muhammad SAW became a mediator in reconciling two people from the Ansor who had a dispute over material rights, fourthly it was found that the Prophet Muhammad SAW justified the arbitration carried out by Abu Syuraikh and Sa'ad Bin Muadz.Keywords: Alternative Dispute Resolution, Al-Qur'an, Al-Hadith